SISTEM HISAB GERHANA BULAN KH. NOOR AHMAD SS DALAM KITAB NÛR AL-ANWȂR - Muhajir, Muhajir (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
This paper presents the lunar eclipse reckoning system in the book Nûr Al-Anwȃr analysis of KH. Noor Ahmad SS. Eclipses are natural events that occur several times each year. In the traditions of the Prophet Muhammad SAW, the event was stated as part of the signs of the greatness of God. The Book of Al-Anwar is one of the books written by the original ulama of the archipelago. The discussion in this book consists of determining the beginning of the Kamariyah month, the lunar eclipse and the solar eclipse. Markaz used in this book is Jepara markaz with coordinates 60 36 'LS and 1100 40'. calculations for other areas must be adjusted slightly.The Book of Al-Anwar includes a system of eclipse reckoning which is quite accurate. The reckoning system was included in the category of essential reckoning bi al-tahqiq. The astronomical data were sourced from al-Ma'la 'al-Sa'id data using the Jepara epoch (110 ° 40' E). The reckoning method uses an ecliptic limit value of 120 and can be scientifically justified. The trigonometric formulas are the result of the modification and transformation of the formula form of the logarithmic formulas in the book of al-Khul'ah al-Wafiyyah into the trigonometry formulas.